A Cobalt Pyrenylnitronylnitroxide Single‐Chain Magnet with High Coercivity and Record Blocking Temperature. Issue 18 (18th March 2014) - Vaz, Maria G. F.; Cassaro, Rafael A. Allão; Akpinar, Handan; Schlueter, John A.; Lahti, Paul M.; Novak, Miguel A.
Abstract Coordination of a [Co(hfac)2] moiety (hfac=hexafluoroacetylacetonate) with a nitronylnitroxide radical linked to bulky, rigid pyrene (PyrNN) gives a helical 1:1 chain complex, in which both oxygen atoms of the radical NO. groups are bonded to CoII ions with strong antiferromagnetic exchange. The complex shows single‐chain magnet (SCM) behavior with frequency‐dependent magnetic susceptibility, field‐cooled and zero‐field‐cooled susceptibility divergence with a high blocking temperature of around 14 K (a record among SCMs), and hysteresis with a very large coercivity of 32 kOe at 8 K. The magnetic behavior is partly related to good chain isolation induced by the large pyrene units. Two magnetic relaxation processes have been observed, a slower one attributable to longer, and a faster one attributable to short chains. No evidence of magnetic ordering has been found.